Cerium(iv) oxide nanoparticles induce sublethal changes in honeybees after chronic exposure. Issue 12 (24th October 2017) - Kos, Monika; Jemec Kokalj, Anita; Glavan, Gordana; Marolt, Gregor; Zidar, Primož; Božič, Janko; Novak, Sara; Drobne, Damjana
Abstract : Oral exposure to up to 500 mg L −1 nCeO2 was sublethal for honeybees but altered the cholinergic system and induced other physiological responses. Abstract : The high annual production and use of cerium(iv ) oxide nanoparticles (nCeO2 s) may lead to their atmospheric release and substantial deposition on plants. This poses a potential threat to pollinators. We investigated the effects of nCeO2 -spiked food (2–500 mg L −1 ) on summer and winter honeybees ( Apis mellifera carnica ) after chronic 9 days' oral exposure. Acetylcholinesterase (AChE) and glutathione S -transferase (GST) activities were measured in different body compartments (heads, thoraces, and haemolymph). The activity of AChE was assessed in salt-soluble (SS) (containing soluble and membrane AChE) and detergent-soluble (DS) (predominantly membrane-bound AChE) fractions. Exposure of honeybees to nCeO2 -spiked food had no significant effects on survival up to 500 mg L −1 (<10%), while significant biochemical alterations were evidenced already at 2 mg L −1 . In summer honeybees, a significant increase in the activities of AChE in the SS fraction and GST was found, while AChE activity in DS fractions was decreased at nearly all exposure concentrations. An exception was the 250 mg L −1 exposure, where AChE activity in DS fractions was increased. The alteration of AChE in the DS fraction could be symptomatic for the affected neuronal system, while alterations of GST activity indicate detoxification processes. An apparent difference in response to nCeO2 was evidenced between the summer and winter honeybees, which is in line with their different physiology. We ascribe most of the observed effects to particulate nCeO2 because a negligible presence of Ce ion species was found in their food. We conclude that nCeO2 release into the environment, especially atmospherically deposited material, is a potential risk to honeybees.